The innovation-driven impact on economic structure transition: The case of China - Hailun Zhang; Sheng Xu (International Journal of Management and Economics, 2017)
The research measures the driving force of innovation in economic structure transition. In order to change the pattern of economic development, China is implementing a strategy of innovation-driven development. China's capacity of innovation has been increasing, especially since 2012, and China's innovations have taken a leap-forward development. Nowadays, innovation has become a main driving force in China's economic development and hi-tech industries particularly make a great contribution. Although China's tertiary industry has been dominant and its share in three industrial sectors has been exceeding 50% since 2015, a problem still exists in China's economy that the proportions of primary and secondary industries are relatively higher compared with developed countries. In this paper we use PLSR model to measure the impact of innovation on China's economic structure transition. It is found that innovation can expand the tertiary industry through shrinking the proportions of primary and secondary industries, transforming China's economic structure into a more advanced pattern. Additionally, China is also devoting itself to the "Belt and Road Initiative", which should be combined with China's domestic innovation-driven development and realize sustainable development of economy worldwide.
Keywords: O39; L16; 650; innovation-driven impact; economic structure transition; tertiary industry; PLSR model; "Belt and Road Initiative"; sustainable development